SELF EFFICACY, INFORMATION ACQUISITION AND UTILIZATION AS CORRELATES OF EFFECTIVE DECISION MAKING AMONG MANAGERS IN INSURANCE COMPANIES IN NIGERIA - S.O., Popoola (Malaysian Journal of Library and Information Science, 2009)
This paper examined the self-efficacy, information acquisition and utilization as correlates of effective decision making of managers in corporate insurance companies in Nigeria. Total enumeration technique called census coupled with a self-developed questionnaire was used to collect data on a population size of 153 managers in eleven corporate insurance companies in Nigeria, out of which 145 responded given a response rate of 94.8 percent. The study found that self-efficacy, information acquisition and utilization had significant collinear relationship with effective decision making of the respondents. In addition, self-efficacy, information acquisition and utilization significantly predict effective decision making of the respondents. More so, each of the independent variables, namely, self-efficacy, information acquisition and information utilization significantly predict effective decision making of the respondents. Nevertheless, information utilization was found to have the greatest percentage (65.22 percent) relative contribution to the prediction of effective decision making of the managers in Nigerian corporate insurance companies.